Performance Modelling of Secure Routing Protocol in Communication Network - Dixit, Mukesh; Dixit, Sarvottam; Sachan, Ajay Kumar (International Journal of Computer Sciences and Engineering, 2025)
A mobile ad hoc network is not a wired network it’s a wireless network that uses multiple hops, peer-to-peer routing in its place of motionless network infrastructure to present network connectivity which is used by consumer for communication. Here, we are discussing and designing newest MANET routing protocols along with is comparisons from previous routing protocol as well as discussed improve version of MANET routing protocols e. g. DYMO is the extended version of AODV and Encrypted DYMO(E-DYMO) is improved version of proposed DYMO; earlier than some routing protocols are synchronized by simulations. Network Simulator (Version 2) present a extremely modular platform intended for wired as well as wireless simulations following different - different network essentials, traffic, protocols, along with routing types. In this work, we get the simulation results in terms of various parameters like throughput, PDR, and E2E delay in terms of security of routing protocol. We also describe comparisons between Enhance DYMO, E-DYMO and proposed DYMO in terms of given parameter as well as shows that the enhance the security of various parameters along with proposed DYMO